The effects of the watsu method on functional capacity, anxiety and depression in patients with parkinson disease - Ribeiro, Ingrid; Lucca, Fernando; Rosa, Thatiane; Maues, Renan; Flor, Sâmia; Souza, Daniele; Dias, George Alberto da Silva; Santos, César Augusto de Souza (Archives in Biosciences & Health, 2019)
Parkinson's disease (PD) is a chronic and progressive pathology that results from the degeneration of the black substance responsible for the voluntary control of movements. The reduction of dopamine generates motor and non-motor symptoms that hinder the mobility of the patient and the execution of their activities of daily living. The Watsu method relieves pain, tension and releases the muscles, fascias and spine leading to the gain of flexibility and range of motion, and can be a facilitator in reducing the symptoms of PD. The aim was to evaluate the effects of the Watsu method on motor and non-motor symptoms and their relation with the functional capacity of these individuals. This is an experimental study applied to 4 male patients diagnosed with PD. The analyzed variables were: anxiety, depression, quality of life, basic and instrumental activities of daily living and balance. 9 Watsu sessions was applied. Student's t-test (paired sample) was carried out to compare the variables studied. There was no significant improvement in the variables analyzed, but there was a tendency for improvement in quality of life variables (before 38.75 and later 36.50), depression (before 23 and after 21.25) and instrumental activities of daily living (before 19.50 and later 20.75). For the variables anxiety, basic activities of daily living and balance there was no improvement of these variables. It was observed that the Watsu method trends to improve motor and no-motor symptoms that affect the PD patients. In addition, there is still a lack in the literature in studies that use the Watsu method as a treatment for both PD and other diseases.